Malaysian youth's views on elements in taking selfie - Lee, Yok Fee; Ab. Majid, Arfah; Adnan, Zatul Himmah (Human Resource Management Academic Research Society, 2022)
The trend of selfies has become a new culture in society. Social networking sites have offered individuals, especially youth, opportunities to present themselves. This study aims to understand what elements Malaysian youth consider when taking a selfie. A sequential mixed method research approach was used first to collect qualitative data through the focused-group discussion method and then by a survey's quantitative data. Two focus group discussions were held to gather the youth's opinions, and the qualitative data were used to build a questionnaire and distributed to 395 youth in Klang Valley of Malaysia. The results show that the youth consider three significant elements, i.e., situational, technical, and social. Among the factors, overall, the technical factor is the most critical (mean = 4.587), followed by the social factor (mean = 4.541) and lastly situational factor (mean = 4.106). However, one of the items in the social factor outstands the others (mean = 5.005). The youths deemed that taking selfies with friends and others without considering their religious and ethnic background is the most important thing. This study concluded that even though the youths pay more attention to how to take a good selfie technically but at the same time, they do consider being inclusive towards other ethnic groups in their social life.